Introducing professional communication skills for undergraduates - Renganathan, Sumathi; Zulqarnain Abu Bakar; Li, Chong Su; Muhammad Ridhuan Tony Lim Abdullah; Azelin Mohamed Noor; Razol Mahari Mohd Ali (Oxford Fajar, 2011)
Introducing Professional Communication Skills for Undergraduates is a textbook specifically written to equip undergraduates with the knowledge and skills needed for successful professional communication during internship or at the workplace. The information presented in this textbook also addresses the many concerns of employers, regarding the poor communication skills of fresh graduates in the English Language. Written in a "conversational" manner by experienced lecturers in the field of Language and Communication, readers are presented with opportunities to critically think about and discuss information, key concepts and issues on the various aspects of professional communication skills. This textbook is an essential resource for undergraduates who are preparing for future employment and can be used as a main textbook for an undergraduate Professional Communication Skills course